PKA and PKC Modulators Affect Ion Channel Function and Internalization of Recombinant Alpha1 and Alpha1-Beta Glycine Receptors - Breitinger, Ulrike; Bahnassawy, Lamiaa M.; Janzen, Dieter; Roemer, Vera; Becker, Cord-Michael; Villmann, Carmen; Breitinger, Hans-Georg (Frontiers in Molecular Neuroscience, 2018)
Glycine receptors (GlyRs) are important mediators of fast inhibitory neurotransmission in the mammalian central nervous system. Their function is controlled by multiple cellular mechanisms, including intracellular regulatory processes. Modulation of GlyR function by protein kinases has been reported for many cell types, involving different techniques, and often yielding contradictory results. Here, we studied the effects of protein kinase C (PKC) and cAMP-dependent protein kinase A (PKA) on glycine induced currents in HEK293 cells expressing human homomeric α1 and heteromeric α1-β GlyRs using whole-cell patch clamp techniques as well as internalization assays. In whole-cell patch-clamp measurements, modulators were applied in the intracellular buffer at concentrations between 0.1 μM and 0.5 μM. EC50 of glycine increased upon application of the protein kinase activators Forskolin and phorbol-12-myristate-13-acetate (PMA) but decreased in the presence of the PKC inhibitor Staurosporine aglycon and the PKA inhibitor H-89. Desensitization of recombinant α1 receptors was significantly increased in the presence of Forskolin. Staurosporine aglycon, on the other hand decreased desensitization of heteromeric α1-β GlyRs. The time course of receptor activation was determined for homomeric α1 receptors and revealed two simultaneous effects: cells showed a decrease of EC50 after 3–6 min of establishing whole-cell configuration. This effect was independent of protein kinase modulators. All modulators of PKA and PKC, however, produced an additional shift of EC50, which overlay and eventually exceeded the cells intrinsic variation of EC50. The effect of kinase activators was abolished if the corresponding inhibitors were co-applied, consistent with PKA and PKC directly mediating the modulation of GlyR function. Direct effects of PKA- and PKC-modulators on receptor expression on transfected HEK cells were monitored within 15 min of drug application, showing a significant increase of receptor internalization with PKA and PKC activators, while the corresponding inhibitors had no significant effect on receptor surface expression or internalization. Our results confirm the observation that phosphorylation via PKA and PKC has a direct effect on the GlyR ion channel complex and plays an important role in the fine-tuning of glycinergic signaling.